Diary of a wimpy kid Old school - Kinney, Jeff (Melbourne, Vic Penguin Books Australia, 2015)
Greg Heffley's town voluntarily unplugs and goes electronics-free. Greg, however, hates the old-fashioned world, and must find a way to survive as tension builds inside and outside the Heffley home
English Stories
For children aged 11 - 15 years
Keywords: Humorous stories; Schools -- Juvenile fiction